Characterization and degradation of a polyaryl ether based superplasticizer for use in concrete barriers in deep geological repositories. (August 2018) - Chernyshev, Alexander N.; Jonsson, Mats; Forsberg, Kerstin
Abstract: Superplasticizers are important additives used in concrete barriers in geological waste repositories. Superplasticizers have been a major concern in the long-term assessments of safe geological disposal for radioactive waste since superplasticizers and their degradation products can act as complexing ligands and thereby increase the mobility of radionuclides. In this work a new type of superplasticizer, based on a polyaryl ether polymer, has been characterized. It was found that the superplasticizer combines the structural features of polycarboxylate ether based superplasticizers and sulfonated naphthalene-formaldehyde based superplasticizers and that it contains organophosphate charged groups. A novel method for evaluating the rate of degradation of the superplasticizer under alkaline conditions was elaborated and the degradation products and rate constant of the process was determined. The results demonstrate that degradation occurs rapidly compared to the typical lifetime of a repository. Graphical abstract: Highlights: The structure of a polyaryl ether based superplasticizer was determined. A method for evaluating degradation of superplasticizers in alkaline media was proposed. The degradation rate constant of a polyaryl ether based superplasticizer was determined.